Bacteriological profile of community‐acquired musculoskeletal infections: a study from Queensland. Issue 10 (27th August 2018) - Matthews, Justin; Bamal, Rahul; McLean, Andrew; Bindra, Randy
Abstract : Background: The purpose of this study was to determine bacteriology of community‐acquired musculoskeletal infections requiring hospitalization and to compare this with published national and international data. This will help treating physicians select the appropriate antibiotic. Methods: All patients who underwent surgical procedures for community‐acquired musculoskeletal infections over a period of 22 months were included in the study. Hospital acquired infections, post‐operative infections and infections involving prosthetic joints were excluded. Patient characteristics, treatment details, cultured organisms and their antibiotic sensitivity were recorded. Results: Forty‐five patients with 46 cases met the inclusion criteria. Ten patients were from paediatric age group. Soft tissue infections were the most common diagnosis and accounted for 20 cases. The remainder were septic arthritis ( n  = 17) and osteomyelitis ( n  = 9). Thirteen patients (28.3%) had negative cultures from the operative samples. Staphylococcus aureus was the most common isolated organism overall accounting for 23 cases (69.7%). Methicillin‐resistant S. aureus (MRSA) sensitive to vancomycin was cultured in four adult cases (12.1%), of which three were hand infections (50%). For the entire cohort, 67.7% and 61.3% isolates that were tested were sensitive to cefazolin and flucloxacillin, respectively. Conclusion: The bacteriological profile in this study is consistent with European and Australian data. While the overall MRSA infection rate was low, it was much higher among hand infections and is comparable to reports from the USA. Flucloxacillin and cefazolin should be considered as the first line of antibiotic therapy for all cases. Vancomycin should be considered when MRSA is suspected.